Is There a Change in the Trade-Off Between Output and Inflation at Low or Stable Inflation Rates? Some Evidence in the Case of Japan - Mourougane, Annabelle (OECD Economics Department Working Papers, 2004)
This paper examines the relationship between the output gap and inflation in Japan by estimating Phillips curves and testing for changes since the advent of low inflation and/or the stabilisation of the rate of change of inflation. The work provides empirical support for the hypothesis of a change in the relationship between output and inflation in an environment of low inflation for Japan. In particular, there is evidence that the slope of the Phillips curve becomes flatter when the inflation rate is below ½ per cent (quarter-on-quarter, non-annualised) and also that there has been a break in the relationship between demand pressures and inflation in Japan since the beginning of the 1990s. Evidence is also found that the relationship changes when the inflation rate is either rising rapidly or falling sharply. At such times, changes in demand pressure have stronger effects on inflation. These results are robust to a wide range of specifications, including corrections for the ...